Solid-state photochemistry: new approaches based on new mechanistic insights - Gerd Kaupp (International Journal of Photoenergy)
The application of atomic force microscopy (AFM) to solid-state photodimerizations revealed previously unexpected long-range molecular movements in the initial stages (phase rebuilding) and in the final stages (phase transformation and disintegration) of reaction. The consequences for the new understanding of solid-state photochemistry are discussed. The 4.2 Å criterion of organic topochemistry lacks a real basis and is not applicable to regular photolyses, even under tail irradiation conditions for instance of α-cinnamic acid or in E/Z-isomerizations in the crystal bulk. The experimental observation of molecular movements in reacting crystals requires more elaborate use of X-ray structural data by invoking the molecular packing. If a crystal keeps its outer form upon photolysis this does not necessarily indicate a topotactic transformation, and submicroscopically resolved AFM investigations are in order. The applications of molecular movements or non-photoreactivities due to the prevention of movements by 3D-interlocked packing have numerous applications. Thus, amorphous solids or inclusion compounds may enable the movements in these cases. Hitherto puzzling E/Z-photoisomerizations in the crystalline state can now be mechanistically understood. In some cases even rotational mechanisms can be modelled in combination with the movements. In others the space saving twist mechanism is the only choice. The benefits of the new solid-state mechanisms for crystal engineering, photochromism, mixed crystals, absolute asymmetric syntheses, and preparative photochemistry derive from its experimental basis. Numerous presumed puzzles from the postulate of minimal atomic and molecular movement vanish in a straightforward manner.